Pengaruh Metode Pembelajaran Index Card Match terhadap Motivasi dan Hasil Belajar Kognitif Siswa SMP - Yuliana, Yayuk (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
This study aims to find out how the Index Card Match learning method influences the motivation and cognitive learning outcomes of students at SMP Negeri 4 Jonggat, Central Lombok Regency. Learning by using the Index Card Match learning method is expected to have students highly motivated in learning to obtain high learning outcomes as well. Through this application it can also make it easier for teachers to improve ways of thinking and increase student involvement in the teaching and learning process. The type of research used in this research is a quasi-experimental (quasi-experimental), this design has a control group, but it does not fully function to control the variables that affect the implementation of the experiment. The experimental class received treatment using the Index Card Match learning method, while the control class used the conventional method. To obtain the necessary data, this study used the t-test analysis technique. From the results of the study, based on the results of the hypothesis testing of the experimental class and the control class using the t-test, the tcount was 0.13 and the ttable was 2.12. This means that the tcount value is smaller than the ttable value or 0.13 <2.12. This shows that Ha is rejected and H0 is accepted, so there is an influence of the Index Card Match learning method on students' motivation and cognitive learning outcomes.